PERENCANAAN DAN PERMODELAN KEBUTUHAN PARKIR UNIVERSITAS SEBAGAI PEMBAHARUAN PEDOMAN PERENCANAAN (STUDI KASUS PUSAT PENDIDIKAN/PERGURUAN TINGGI) - Irfan Abdulhafizh Karnaen (Jurnal Manajemen Dirgantara, 2023)
Guidelines for planning parking facilities have been regulated in the Guidelines for Planning and Operation of Parking Facilities, Director General of Land Transportation but this reference can be said to be past to be used as a guideline, because considering the development of the type, type and number of motorized vehicles growing so rapidly, the size of the unit needs of parking space for each activity center needs to be tested again, in this case, researchers are trying to conduct a survey at the education center / university to provide a foundation which has the potential to be used as a reference for parking planning policies. There were two dependent variables (Y) used in this study: maximum parking accumulation of cars and motorcycles. These two variables were obtained from vehicle surveys conducted using the survey cordon method. However, the independent variable consists of the number of students (X1), the number of lecturers (X2), and the number of education staff (X3). The study used regression analysis, and the SPSS program was used to create and test the model. The results of the analysis obtained the best model for car Y = 29.963 + 0.773 X2 + 0.474 X3 with R2 0.996, for motorcycle Y = 468.577 + 0.380 X1 + -9.608 X3 with R2 0.995. Both models were selected based on significant, simultaneous, normality, linearity, and multicollinearity tests. The results show that both models meet the BLUE criteria, meaning at best, linearity, unbiased, and estimator.